TIP30 overcomes gefitinib resistance by regulating cytoplasmic and nuclear EGFR signaling in non–small‐cell lung cancer. Issue 10 (10th August 2021) - Shuai, Shuai; Liao, Xueyang; Wang, Haixia; Liu, Lusha; Mei, Shiqi; Cao, Jiaxin; Wang, Senming
Abstract: Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) (eg, gefitinib) exert potent therapeutic efficacy in non–small‐cell lung cancer (NSCLC) harboring EGFR‐activating mutations. However, the resistance to EGFR TKIs limits their clinical therapeutic efficacy. TIP30, a newly identified tumor suppressor, appears to be involved in the regulation of cytoplasmic and nuclear EGFR signaling in NSCLC. Our previous study demonstrated that TIP30 regulated EGF‐dependent cyclin D1 transcription in human lung adenocarcinoma and suppressed tumorigenesis. In the present study, the involvement of TIP30 in combating gefitinib resistance in NSCLC was determined for the first time in vitro and in vivo. Gain and loss of function studies showed that overexpression of TIP30 effectively sensitized cells to gefitinib in vitro, whereas TIP30 inhibition promoted gefitinib cell resistance. Moreover, TIP30 negatively regulated the activation of the p‐AKT and p‐MEK signaling pathways in PC9/GR. Importantly, PC9/GR harbored high levels of nuclear EGFR, and overexpression of TIP30 restored irregular EGFR trafficking and degradation from early endosomes to the late endosomes, decreasing the nuclear accumulation of EGFR, which may partly or totally inhibit EGFR‐mediated induction of c‐ Myc transcription. Xenographic tumors induced by overexpression of TIP30 by PC9/GR cells in nude mice were suppressed compared with their original counterparts. Overall, it was revealed that TIP30 overexpression restored gefitinib sensitivity in NSCLC cells and attenuated the cytoplasmic and nuclear EGFR signaling pathways and may be a promising biomarker in gefitinib resistance in NSCLC. Abstract : This work investigated the vital role of TIP30 in gefitinib resistance of NSCLC‐involved modulation of the nuclear EGFR signaling pathway. Findings indicated that a low TIP30 level may confer gefitinib resistance and overexpression of TIP30 may predict a favorable response to gefitinib‐based chemotherapy in NSCLC.